1987
DOI: 10.1113/jphysiol.1987.sp016722
|View full text |Cite
|
Sign up to set email alerts
|

The effect of treadmill speed on ventilation at the start of exercise in man.

Abstract: SUMMARY1. The change in ventilation at the start of exercise was determined during both hyperoxic rebreathing and air breathing in four volunteers.2. In order to differentiate between the effects of limb-movement frequency and exercise load in terms of oxygen uptake, three treadmill exercises were tested: El, at an oxygen uptake of 1 1/min on a level treadmill; E2, at 2 1/min on an inclined treadmill at the same speed as El; E3, at 2 1/min on a level treadmill at a higher speed. All of the exercises were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 37 publications
(51 reference statements)
1
20
2
Order By: Relevance
“…Moreover several investigators have found that for the same increase in metabolic rate, the tachypnea and hyperpnea are greater when the treadmill speed or cycling frequency is increased as opposed to an increase in treadmill grade or cycling resistance (5,32,53,67,179,193,194,242). Furthermore during sinusoidal changes in work rate, investigators have found greater amplitudes and lower phase lags for ventilation when limbmovement frequency is varied compared to variations in treadmill grade or cycle resistance (64,65,342).…”
Section: Breathing Frequency and Limb-movement Frequencymentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover several investigators have found that for the same increase in metabolic rate, the tachypnea and hyperpnea are greater when the treadmill speed or cycling frequency is increased as opposed to an increase in treadmill grade or cycling resistance (5,32,53,67,179,193,194,242). Furthermore during sinusoidal changes in work rate, investigators have found greater amplitudes and lower phase lags for ventilation when limbmovement frequency is varied compared to variations in treadmill grade or cycle resistance (64,65,342).…”
Section: Breathing Frequency and Limb-movement Frequencymentioning
confidence: 92%
“…First, this response is greater for the same workload when it is achieved by treadmill speed rather than treadmill grade (32,67,78). Second, the behavioral or arousal state appears important as the rapid response is attenuated when humans at the onset of exercise are engaged in a complex cognitive task (34,36).…”
Section: Theories On the Mechanisms Mediating The Exercise Hyhperpneamentioning
confidence: 98%
“…It has been reported that the ventilatory response at the onset of the exercise is variable in magnitude. That is, the phase I is in¯uenced by various factors, such as light and moderate exercise (Casaburi et al 1978;Whipp et al 1982), posture (Karlson et al 1975;Weiler-Ravell et al 1982), exercise frequency (Casey et al 1987;Kelsey and Dun 1992), or exercise intensity (Cummin et al 1986;Miyamura et al 1992). In addition to the above factors, the ventilatory response at the onset of exercise has also been considered to be modi®ed by heredity, environment, sex and age.…”
Section: Introductionmentioning
confidence: 96%
“…The exertion level determines the final steady-state ventilation for a constant workload and has been related to muscle activity (Dejours 1964;Duffin 1994). Experiments have determined ventilatory and physiologic responses to varying exercise profiles and modes Duffin 2004, 2006;Casey et al 1987;Diamond et al 1977;Mateika and Duffin 1992;Miyamoto and Niizeki 1992;Pearce and Milhorn 1977;Sato et al 2004;Wasserman and Whipp 1983), exercise intensities (Mateika and Duffin 1992;Miyamoto et al 1982), exercise in unfavorable environments such as simulated altitude (Wagner et al 1986), low oxygen (Bechbache et al 1979), and carbon monoxide exposure (Ekblom and Huot 1972).…”
Section: Introductionmentioning
confidence: 98%
“…Ventilatory response is modulated by gas exchange kinetics, gas transport, and muscle metabolic activity factors which are highly dependent on the initial work conditions, activity, and exertion level (Mateika and Duffin 1995;Wasserman et al 1986;. Initiation of dynamic exercise from rest has been shown to produce a sudden increase in ventilation proportional to frequency of limb movement and the magnitude of workload (Broman and Wigertz 1971;Casey et al 1987;Cunningham 1967;Dejours 1964;Krogh and Lindhard 1913;Linnarsson 1974;Whipp and Wasserman 1972). The exertion level determines the final steady-state ventilation for a constant workload and has been related to muscle activity (Dejours 1964;Duffin 1994).…”
Section: Introductionmentioning
confidence: 99%